Fluoride release and fluoride-recharging ability of three different sealants - Patil, Sneha; Kontham, Ujwal R.; Kontham, Rakesh K.; Patil, Smita S.; Kamble, Sanjay P. (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2020)
Background: We aimed to determine the fluoride release and fluoride-recharging ability of a sealant containing surface pre-reacted glass (S-PRG) ionomer filler particles (BeautiSealant) with a fluoride-releasing resin sealant (Helioseal F), and a glass-ionomer sealant (Fuji VII). Materials: And: Methodology: Forty-eight disc-shaped specimens of each material were immersed in deionized water to determine the fluoride release utilizing a fluoride ion-selective electrode. After 21 days, 8 specimens were soaked in 0.22% Sodium Fluoride solution for 2 min; 8 specimens were coated with 1.23% Acidulated Phosphate Fluoride (APF) gel for 4 min, and the fluoride-recharging ability was evaluated for 40 days. Data were analyzed using one way-ANOVA and Bonferroni post hoc tests. Results: Total fluoride release over the 21-day period was: Fuji VII > BeautiSealant > Helioseal F, (P = 0.000). After refluoridation of the specimens with 0.22% Sodium Fluoride solution, the cumulative fluoride release during the 40-day period for each material was: BeautiSealant > Fuji VII > Helioseal (P = 0.000). After exposure to 1.23% APF gel, the cumulative fluoride release during the 40-day period for each material was: BeautiSealant > Fuji VII > Helioseal F (P = 0.000). Conclusion: Glass ionomer-based sealants (Fuji VII) exhibited higher initial fluoride release whilst the surface pre-reacted glass-ionomer filler containing sealant (BeautiSealant) demonstrated superior fluoride recharging properties.